2011
DOI: 10.1186/1471-2458-11-s3-s3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to screen and manage infections during pregnancy on reducing stillbirths: a review

Abstract: BackgroundInfection is a well acknowledged cause of stillbirths and may account for about half of all perinatal deaths today, especially in developing countries. This review presents the impact of interventions targeting various important infections during pregnancy on stillbirth or perinatal mortality.MethodsWe undertook a systematic review including all relevant literature on interventions dealing with infections during pregnancy for assessment of effects on stillbirths or perinatal mortality. The quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(36 citation statements)
references
References 85 publications
0
34
0
2
Order By: Relevance
“…40 However, limited research is available on the effect of HAART on fetal death 41 and a recent pooled analysis of studies showed that HAART did not reduce the possibility of stillbirths. 42 In our study, in spite of the better CD4 counts at the time of pregnancy due to treatment (HAART), the group of women who received HAART might be clinically different than the women who received AZT. However, a recent study by Baroncelli and colleagues 43 among women who were diagnosed before pregnancy and undergoing ART at conception reported that women who have not experienced AIDS-defining events have similar maternal and neonatal outcomes as compared to women with more advanced stage of the disease.…”
Section: Darak Et Almentioning
confidence: 81%
“…40 However, limited research is available on the effect of HAART on fetal death 41 and a recent pooled analysis of studies showed that HAART did not reduce the possibility of stillbirths. 42 In our study, in spite of the better CD4 counts at the time of pregnancy due to treatment (HAART), the group of women who received HAART might be clinically different than the women who received AZT. However, a recent study by Baroncelli and colleagues 43 among women who were diagnosed before pregnancy and undergoing ART at conception reported that women who have not experienced AIDS-defining events have similar maternal and neonatal outcomes as compared to women with more advanced stage of the disease.…”
Section: Darak Et Almentioning
confidence: 81%
“…63 In practical terms, however, both interventions are used in combination in endemic populations, which reduces the risk of stillbirths in women in their fi rst or second pregnancy by an estimated 22% (table 1). 21 …”
Section: Comprehensive Emergency Obstetric Carementioning
confidence: 99%
“…3 Antenatal screening and treatment of maternal infection can substantially reduce stillbirth rates, as evidenced by programmes to prevent congenital syphilis that are estimated to have reduced syphilis-related stillbirth rates by up to 80%. [3][4][5] The role of other in utero fetal infections in stillbirths, however, is less well documented, and would be important to delineate to further improve pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%